Indigenous knowledge on camel milk and camel milk products hygienic handling, processing and utilization in Borana Area, Southern Ethiopia - Birhanu Bekele; Anaf Oneta; Adem Kumbe; Beshir Husein (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2021)
The study was conducted to assess traditional camel milk and camel milk products handling, preservation and processing, as well as utilization in Borana area. A total of 132 and 24 respondents were selected from milk producers and supplies, respectively through purposive sampling technique and interviewed on various aspects of camel milk and camel milk products using a single-visit multiple-subject diagnostic survey. Survey results revealed that the majority of camel dairying was done by women. Result showed hygienic handling of camel milk and milk products of pastoralists and agro-pastoralists was poor. Respondents reported that they preserved camel milk by washing and smoking milk vessels, keeping milk in a cold place and processing into other milk products. All most all respondents use camel milk mainly in its raw state for home consumption. Most of the respondents in the study area traditionally process camel milk into other camel milk products mainly during surplus milk production. The major product produced by respondents was fermented sour camel milk, locally named chuuchee. According to respondents lack of cooling facilities, improper collection center, lack of milk collection equipment, market milk selling shed, quick spoilage of milk due to the hot environment, seasonality of milk supply and marketing are the main constraints. Establishment of milk collection centers and introduction of small-scale milk processing plants with market linkage might help to solve camel milk hygienic handling and marketing problems in the study area.